Psychosis in Alzheimer's Disease Is Associated With Increased Excitatory Neuron Vulnerability and Post-transcriptional Mechanisms Altering Synaptic Protein Levels - DeChellis-Marks, Michael R.; Wei, Yue; Ding, Ying; Wolfe, Cody M.; Krivinko, Joshua M.; MacDonald, Matthew L.; Lopez, Oscar L.; Sweet, Robert A.; Kofler, Julia (Frontiers in Neurology, 2022)
1 Abstract Alzheimer’s disease with psychosis (AD+P) is a heritable phenotypic variant of the disease which is associated with more rapid cognitive deterioration compared to Alzheimer’s disease without psychosis (AD-P). Cognitive decline in AD correlates with synapse loss, and our previous studies suggest that those with AD+P have a differentially affected synaptic proteome relative to those with AD-P. In this study, we utilized RNA-sequencing of dorsolateral prefrontal cortex (DLPFC) in a cohort of 80 AD cases to evaluate novel transcriptomic signatures that may confer risk of psychosis in AD. We found that AD+P was associated with a 9% reduction in excitatory neuron proportion compared to AD-P [Mean (SD) AD+P 0.295 (0.061); AD-P 0.324 (0.052), p = 0.026]. mRNA levels contributed only modestly to altered synaptic proteins in AD+P relative to AD-P. Instead, network analysis identified altered expression of gene modules from protein ubiquitination, unfolded protein response, eukaryotic initiation factor 2 (EIF2) signaling and endoplasmic reticulum stress pathways in AD+P. We previously found that neuropathologies account for approximately 18% of the variance in the occurrence of psychosis in AD. Further inclusion of cell type proportions and differentially expressed modules increased the percent of the variance in psychosis occurrence accounted for in our AD cohort to 67.5%.